Gotham Academy. Volume 2, Calamity - Cloonan, Becky; Fletcher, Brenden (DC Comics, 2016)
A collection of graphic novel stories featuring the kids of Gotham Academy. First Olive begins seeing ghosts and delves into the secret of her mother's death. Then the students hunt a werewolf on the school grounds, and Maps meets the new transfer student, Damian Wayne.